Virtual shopping agents: Persona effects for older users. Issue 2 (3rd June 2014) - Chattaraman, Veena; Kwon, Wi-Suk; E. Gilbert, Juan; Li, Yishuang
Abstract : Purpose: – The purpose of this study is to investigate whether the visual presence of a virtual agent on a retail Web site reveals positive outcomes for older users with respect to enhancing perceived interactivity, social support, trust and patronage intentions and alleviating user anxiety. Design/methodology/approach: – A between-subjects laboratory experiment was conducted with 50 older users, which included an interaction experience of 30 minutes followed by a paper-based questionnaire. The visual presence of the agent was manipulated in a mock retail Web site through the presence or absence of a virtual agent image, while maintaining the same agent functionality. Findings: – The contrasts of senior users' shopping experiences between two agent-mediated Web sites (with or without agent image) support the direct "persona" effects of a virtual agent's visual presence on enhancing perceived interactivity, social support, trust and patronage intentions in the retail Web site, while alleviating user anxiety. Further, anxiety alleviation is fully explained by increased perceptions of interactivity. Perceived social support fully mediates trust in the benevolence of the online retailer. Trust ability emerges as a salient factor mediating the relationship between agent persona and patronage intentions. Originality/value: – This work is the first to identify the value of human visual embodiment for older users' online shopping experiences, which has implications for other low-experience/expertise users of a medium.